Kendra Keely: capstone - Keely, Kendra, artist (Colorado State University. Libraries, 2016)
The artist's statement: Jerry Uelsmann once said while talking about the creative nature of his art, "My visual quest is driven by a desire to create a universe capable of supporting feelings and ideas." My work is heavily influenced by this and created with the desire to express feelings and the psychological state of being. Creating images that defy reality open up the possibility to create a world more meaningful than the one we experience. I want my work to elicit and express the unseen emotions that can be experienced while everything else around us is covered by the smoke of reality.
Fading
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photography